Resource utilization of municipal solid waste incineration fly ash in iron ore sintering process: A novel thermal treatment. (1st August 2020) - Wong, Guojing; Fan, Xiaohui; Gan, Min; Ji, Zhiyun; Ye, Hengdi; Zhou, Zhian; Wang, Zhaocai
Abstract: High calcium in the municipal solid waste incineration (MSWI) fly ash made it a potential material for replacing part of the calcium flux used in iron ore sintering process. The results show that the sintering indexes were not negative affected but improved slightly as MSWI fly ash added, which is mainly because the ultra-fine material helped to obtain a better granulation and produced liquid phase under high temperature. Removal rates of harmful elements were improved as the increased content of chlorine brought in by the MSWI fly ash, which means that the residual contents of K, Na, Pb and Zn in the finished sinter were not increased significantly. 93.03% of the dioxins in the MSWI fly ash was degraded due to the fast heating rate and high temperature during sintering process, both of which are favorable factors for the degradation of dioxins. Although the addition of the MSWI fly ash made the concentration of SO2 and dioxins in the flue gas increased, standardized discharge can still be realized through conventional activated carbon system for flue gas purification. Therefore, the resource utilization and harmless disposal of MSWI fly ash can be realized through iron ore sintering process. Graphical abstract: Image 1 Highlights: Sintering indexes were not deteriorated but improved as MSWI fly ash added. Harmful elements brought in by MSWI fly ash were not increased in finished sinter. 93.03% of 17 toxic dioxins in MSWI fly ash can be degraded in sintering process. MSWI fly ash, a hazardous material, can be treated by iron ore sintering process.